Rancang Bangun Sistem Informasi Geografis Pariwisata Berbasis Web Studi Kasus Kabupaten Bandung - Sutedi, Ade; Heryanto, Deni; Hidayat, Miftahul (Jurnal Algoritma, 2023)
One of the most sought after information currently is tourist attractions in an area. In the last year, Bandung Regency has had new tourist destinations which are emerging rapidly. To manage this tourist location, Bandung district has an information system, but this system still has limitations. Therefore, it is necessary to develop a tourism information system that is more detailed and can provide convenience for the Bandung Regency Culture and Tourism Office in managing and presenting tourism information. The aim of this research is to design and build a Tourism Geographic Information System in Bandung Regency. The development methodology used is the Rational Unified Process (RUP). The result of this research is a Tourism Geographic Information System which features information on tourist destinations including ticket prices, vehicle access and routes to tourist locations. Apart from that, this system also includes information on accommodation and restaurants around tourist destinations. Thus, this Tourism Geographic Information System can be used as a reference source of information on tourist destinations, especially for tourists in Bandung Regency.